Variability on particulate matter and meteorology dataset during the hazy period in eastern region of Peninsular Malaysia - Ku Yusof, Ku Mohd Kalkausar; Ismail, Siti Sofo; Azid, Azman; Abdullah Sani, Muhamad Shirwan; Isa, Noorain Mohd; Mohamat Zawawi, Mohd Zulfahmie (Elsevier Inc., 2020)
This paper provides detail on sequence analysis of hazy days based on eight monitoring stations from three states (Kelantan, Ter- engganu and Pahang) in the eastern region of Peninsular Malaysia. The dataset comprises of 1502 daily mean hazy days that had been measured for a decade. The meteorology data namely wind speed, wind direction, air temperature, relative humidity and particulate matter (PM10) were used to comprehend the variability, and the relationship existed amongst variables. The final dataset consists of a summary descriptive analysis and a boxplot, where all five var- iables were involved, including the minimum, maximum, mean, 1st quartile, median, 3rd quartile and standard deviation are pre- sented. Apart from descriptive analysis, the normality test and histogram were performed as well.